"Ecological" and Highly Demanding Executive Tasks Detect Real-Life Deficits in High-Functioning Adult ADHD Patients. (January 2013) - Torralva, Teresa; Gleichgerrcht, Ezequiel; Lischinsky, Alicia; Roca, María; Manes, Facundo
Objective: Many adult ADHD patients with a convincing history of real-life executive deficits perform entirely within normal limits or with minimally impaired performance in classical executive tests. The authors assessed a group of high cognitive functioning adult ADHD participants on "ecological" and "highly demanding" executive tasks.Method: A total of 117 adult ADHD participants were classified as showing either a high-functioning (Hi-ADHD) or a low-functioning (Lo-ADHD) neuropsychological profile based on standard assessment. Their performance was compared with healthy controls ( n = 21) on an ecological task of executive function (the hotel task) and computerized tasks of high cognitive demand.Results: Lo-ADHD significantly differed from controls on multiple standard neuropsychological variables as well as on the experimental tasks. Hi-ADHD and healthy controls did not differ significantly on any of the standard neuropsychological variables, but a significant difference was found between the groups on measures of the experimental tasks.Conclusion: Real-life executive dysfunction of patients with ADHD who perform within normal range on standard assessment can be detected with the use of more ecological and highly demanding tasks.